2018
DOI: 10.3389/fphar.2018.01327
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects on Vascular Smooth Muscle Cell Proliferation and Macrophage-induced Inflammation Reveal a Protective Role for the Proresolving Lipid Mediator Receptor ChemR23 in Intimal Hyperplasia

Abstract: Intimal hyperplasia remains a significant clinical problem in for example coronary artery bypass graft failure. Since omega-3 fatty acids reduce intimal hyperplasia, we hypothesized that the G protein-coupled receptor ChemR23 for the omega-3-derived pro-resolving lipid mediator resolvin E1 drives those effects. ChemR23+/+ and ChemR23-/- mice were generated with or without introduction of the Caenorhabditis elegans fat-1 transgene, which leads to an endogenous omega-3 fatty acid synthesis and thus increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…In addition, previous studies had indicated a role of CmklR1 for the vascular smooth muscle cell (VSMC) atherosclerotic phenotype [47], characterized by vascular inflammation and intimal hyperplasia [48,49]. Surprisingly, chemerin seemed to inhibit atherogenesis through CmklR1 [48,50]. Carracedo et al [51] were able to show that chemerin treatment of isolated wild-type mouse VSMCs significantly reduced phosphate-induced calcification and increased expression of the calcification inhibitor matrix-gla-protein (MGP).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous studies had indicated a role of CmklR1 for the vascular smooth muscle cell (VSMC) atherosclerotic phenotype [47], characterized by vascular inflammation and intimal hyperplasia [48,49]. Surprisingly, chemerin seemed to inhibit atherogenesis through CmklR1 [48,50]. Carracedo et al [51] were able to show that chemerin treatment of isolated wild-type mouse VSMCs significantly reduced phosphate-induced calcification and increased expression of the calcification inhibitor matrix-gla-protein (MGP).…”
Section: Discussionmentioning
confidence: 99%
“…This seems controversial, as CKD induces premature vascular aging with vascular calcification and increased arterial stiffness [46]. In addition, previous studies had indicated a role of CmklR1 for the vascular smooth muscle cell (VSMC) atherosclerotic phenotype [47], characterized by vascular inflammation and intimal hyperplasia [48,49]. Surprisingly, chemerin seemed to inhibit atherogenesis through CmklR1 [48,50].…”
Section: Discussionmentioning
confidence: 99%
“…RvE1 signals through ChemR23 34 and has been shown, for example, to reduce atherosclerosis 9 and intimal hyperplasia. 10 , 35 RvE1-induced effects on macrophages include decreasing inflammation, inhibiting oxidized low-density lipoprotein uptake, and increasing phagocytosis. 9 Those proresolving actions are stimulated by a macrophage polarization toward an M2-like or intermediate phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the incubation periods, total VIC RNA was isolated as described above. Real-time PCR was performed on a 7900HT Fast RealTime PCR system (Perkin-Elmer Applied Biosystems, Norwalk, CT, USA) as previously described [19] using Taqman Assay-on-Demand (Thermo Fisher Scientific, Waltham, MA, USA) for PRG4 (Hs00981633_m1), BMP2 (Hs00154192_m1), RUNX2 (Hs00231692_m1). and SRY-Box transcription factor 9 (SOX9) (Hs00165814_m1).…”
Section: Valve Interstitial Cells (Vic) Treatments and Real-time Pcrmentioning
confidence: 99%